Mutant α-Synuclein Overexpression Mediates Early Proinflammatory Activity - Su, Xiaomin (2009)
Microglia provide immune surveillance for the brain through both the removal of cellular debris and protection against infection by microorganisms and “foreign” molecules. Upon activation, microglia display an altered morphology and increased expression of proinflammatory molecules. Increased numbers of activated microglia have been identified in a number of neurodegenerative diseases including Parkinson's disease (PD). What remains to be determined is whether activated microglia result from ongoing cell death or are involved in disease initiation and progression. To address this question we utilized a transgenic mouse model that expresses a mutated form of a key protein involved in Parkinson's disease, α-synuclein. Herein, we report an increase in activated microglia and proinflammatory molecules in 1-month-old transgenic mice well before cell death occurs in this model. Frank microglial activation is resolved by 6 months of age while a subset of proinflammatory molecules remain elevated for 12 months. Both tyrosine hydroxylase mRNA expression and α-synuclein protein are decreased in the striatum of older animals evidence of dystrophic neuritic projections. To determine whether mutated α-synuclein could directly activate microglia primary microglia-enriched cell cultures were treated with exogenous mutated α-synuclein. The data reveal an increase in activated microglia and proinflammatory molecules due to direct interaction with mutated α-synuclein. Together, these data demonstrate that mutated α-synuclein mediates a proinflammatory response in microglia and this activity may participate in PD pathogenesis.